Development of bismuth-nickel oxide and bismuth-zinc oxide catalsyts for biodiesel production from crude palm oil - Yew, Sook Yan (2019)
The depletion of non-renewable petroleum reserve, the consequent rising price of diesel as well as environmental concerns about air pollution caused by the combustion of conventional fuel has stimulated the interest on the development of alternative fuel. Biodiesel is a suitable substitute for petrol-based diesel that can be used directly in transports without engine modifications and it has a nearly same engine performance as petrol-diesel. However, the cost of biodiesel production mostly contributed from the cost of feedstock applied. Thus biodiesel production from crude palm oil is very crucial to reduce the cost and its compatibility and reusability with the suitable acid catalyst. In this study, varying composition of bismuth-nickel oxide (Bi-Ni) and bismuth-zinc oxide (Bi- Zn) catalysts were prepared using wet impregnation method. They were characterized by thermal gravimetric analysis (TGA), X-ray diffraction (XRD), X-ray fluoroscopy (XRF), Brunauer-Emmett-Teller (BET) surface area analysis, temperature programmed desorption of ammonia gas (TPD-NH3), fouriertransform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The catalytic performances of the mixed oxides were evaluated in simultaneous transesterification and esterification of free fatty acid containing crude palm oil under effects of composition of bismuth oxide, reaction temperature, reaction time, amount of catalyst and methanol to oil molar ratio. The optimum reaction conditions for Bi-Ni catalyst were at 200°C, 5 wt.% of catalyst, methanol/oil molar ratio of 30:1 and 5 h of reaction time to obtain 91.77% of yield. The reusability test of Bi-Ni shows that it can be used under the same reaction conditions for 6 times continuously before it decreased to 75.00% in the 7th run. For Bi-Zn catalyst system, 92.55% of biodiesel was achieved under 180°C with the methanol to oil molar ratio of 30:1 when 5 wt.% catalyst was added and run for 5 hours. Bi-Zn showed a higher reusability and stability since it only decreased to 76.21 % of yield after 7th runs continuously. Biodiesel production was optimized using response surface methodology (RSM). Bi-Ni achieved optimum biodiesel yield of 92.43% under the following reaction conditions: reaction temperature: 193.26°C, reaction time: 5.34 h, catalyst amount: 5.15 wt.%, methanol to oil molar ratio: 30.18:1. Besides, under the reaction temperature: 186.97°C, reaction time: 5.24 h, catalyst amount: 5.10 wt.%, methanol to oil molar ratio: 31.91:1, the optimum biodiesel yield achieved by Bi-Zn catalyst was 95.10%. In conclusions, the high biodiesel yield using Bi-Ni and Bi-Zn catalysts and the accuracy of the 3 dimensional (3D) models between reaction parameters in RSM shows promising results and optimized yield achieved. The high reusability of both catalysts shows the high stability of the catalysts.